Natural Variation in Monoterpene Synthesis in Kiwifruit: Transcriptional Regulation of Terpene Synthases by NAC and ETHYLENE-INSENSITIVE3-Like Transcription Factors. Issue 4 (3rd February 2015) - Nieuwenhuizen, Niels J.; Chen, Xiuyin; Wang, Mindy Y.; Matich, Adam J.; Perez, Ramon Lopez; Allan, Andrew C.; Green, Sol A.; Atkinson, Ross G.
Abstract : Fruit monoterpene synthesis in kiwifruit is transcriptionally regulated by transcription factors that activate the terpene synthase promoter. Abstract: Two kiwifruit ( Actinidia ) species with contrasting terpene profiles were compared to understand the regulation of fruit monoterpene production. High rates of terpinolene production in ripe Actinidia arguta fruit were correlated with increasing gene and protein expression of A. arguta terpene synthase1 ( AaTPS1 ) and correlated with an increase in transcript levels of the 2-C-methyl-d -erythritol 4-phosphate pathway enzyme 1-deoxy-d -xylulose-5-phosphate synthase ( DXS ). Actinidia chinensis terpene synthase1 ( AcTPS1 ) was identified as part of an array of eight tandemly duplicated genes, and AcTPS1 expression and terpene production were observed only at low levels in developing fruit. Transient overexpression of DXS in Nicotiana benthamiana leaves elevated monoterpene synthesis by AaTPS1 more than 100-fold, indicating that DXS is likely to be the key step in regulating 2-C-methyl-d -erythritol 4-phosphate substrate flux in kiwifruit. Comparative promoter analysis identified potential NAC (for no apical meristem [NAM], Arabidopsis transcription activation factor [ATAF], and cup-shaped cotyledon [CUC])-domain transcription factor) and ETHYLENE-INSENSITIVE3-like transcription factor (TF) binding sites in the AaTPS1 promoter, and cloned members of both TF classes were able to activate the AaTPS1 promoter in transient assays. Electrophoretic mobility shift assays showed that AaNAC2, AaNAC3, and AaNAC4 bind a 28-bp fragment of the proximal NAC binding site in the AaTPS1 promoter but not the A. chinensis AcTPS1 promoter, where the NAC binding site was mutated. Activation could be restored by reintroducing multiple repeats of the 12-bp NAC core-binding motif. The absence of NAC transcriptional activation in ripe A. chinensis fruit can account for the low accumulation of AcTPS1 transcript, protein, and monoterpene volatiles in this species. These results indicate the importance of NAC TFs in controlling monoterpene production and other traits in ripening fruits.